The Conflict of the Great Powers (France, United Kingdoms and Russia) on Iran during the Fath-Ali Shah Qajar (1797-1843) - Bakhtear Saeed Mahmood (Zanco Journal of Humanity Sciences)
The era of Fath-Ali Shah Qajar is regarded as the most important period of a Qajar’s history. Fath-Ali Shah was a second ruler in Qajar’s dynasty. He took a power in 1798 after a death of Agha Muhamad Khan. He was ruled for over 37 years. The most important event that occurred during his rule, was a conflict between the great powers such as France, Russia and Britain on Iran, at the beginning of 19th century, which had a great impact on Iran’s foreign relations. Iran’s foreign relations expanded very widely during his rule, especially during Napoleon’s era in France and his conflicts in with European powers. After that the European countries paid more attention to Iran, to protect their interests in the region. These events need more study and researches.